H Hubungan Health Locus of Control Terhadap Tingkat Kepatuhan Kontrol Glikemik Pada Pasien Diabetes Melitus Tipe 2 di Puskesmas Terminal Banjarmasin - Onieqie Ayu Dhea Manto; Rico Naim; Cynthia Eka Fayuning Tjomiadi (LPPM Universitas Sari Mulia, 2022)
Background: Diabetes mellitus is a chronic disease caused by the pancreas not being able to produce enough insulin for the body. One of the pillars of diabetes mellitus treatment is glycemic control with a health locus of control which is rarely realized in the process control. Objective: To determine the relationship between health locus of control and the level of glycemic control compliance in patients with type 2 diabetes mellitus at the Banjarmasin Terminal Health Center. Method: his study uses quantitative methods and uses a cross sectional study approach. The number of samples as many as 73 people with purposive sampling technique. Result: Spearman's rho correlation test results with = 0.05. From the results of the Spearman's rho statistical test, a significant value of 0.198> 0.05 showed that there was no relationship between health locus of control and the level of glycemic control compliance. Conclusion: Compliance is not only influenced by health locus of control but also influenced by other factors such as medication administration, diet, physical activity or foot care.